The Big Poo Review: A ZOE Health Study Deep Dive into the UK’s Bowel Habits - Inbar Linenberg; Kate Bermingham; Arnab Pushilal; Tim Spector; Jonathan Wolf; Sarah Berry; William Bulsiewicz (Proceedings)
Background: Bowel habits remain under-studied despite their associations with chronic diseases and their impact on quality of life. We aimed to elucidate the pattern of bowel habits in the UK and investigate gender differences and dietary associations. Methods: A UK population-based survey, “The Big Poo Review,” involving 142,765 participants, was conducted in the ZOE Health Study (LRS/DP-20/21-25809). Respondents completed a 37-item bowel habit questionnaire. Diarrhoea was defined as evacuation >3 times/day or passing Bristol Stool scale (BSS) type 6 or 7 > 25% and constipation was defined as evacuation <3 times/wk or passing BSS type 1 or 2 > 25%. Participants (n = 26,703) who completed a food frequency questionnaire within 5 months of the study were included in the subgroup dietary analysis. Results: Participants were predominantly female (77%) with a mean age of 57.8 years (IQR: 50–67). The most frequently reported bowel pattern was a single daily bowel movement (54%) after breakfast (60%) and BSS type 4 (40%). The mean defecation frequency was 1.7 times/day (SD 0.9), but 0.4% of participants defecated <1 time/wk and 1.4% defecated >4 times/day. Constipation was reported in 21.0% (women 23.3%, men 13.0%; p < 0.001) and diarrhoea in 15.3% (men 17.5%, women 14.7%; p < 0.001). Those with diarrhoea or constipation consumed significantly fewer legumes, nuts, and seeds (12 g and 7 g/day less, respectively), fruits (14 g and 18 g/day less, respectively), and vegetables (14 g and 30 g/day less, respectively) than those without (p < 0.01 for all comparisons). Dairy intake was different between all three groups (constipation 276 g/day; diarrhoea 256 g/day; regular stools 267 g/day; p < 0.001 for all comparisons). Discussion: This survey is the largest study of UK bowel habits to date, highlighting gender and dietary differences in habits. The high prevalence of constipation and diarrhoea underscores the need for focused public health efforts and potential nutrition interventions.